Building counting by traditional game: Mathematics Program for Young Children - Nasrullah Nasrullah; Zulkardi Zulkardi (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2011)
In line with design research, the use of Bermain Satu Rumah (BSR) as traditional game to support children’s counting classroom wherein students are encouraged to construct mathematical understanding. Number in traditional games is an interesting aspect that is helpful for children to encounter numerous situations that bring them into contact with sounds, symbols and meanings that relate to numbers. Bermain satu rumah as starting activity would be media to enhance student’s sense of number as well as to be used as learning material. By developing model-of problem of bermain satu rumah as traditional context, resultative counting is counting a number of things with the aim of determining how many are there (the result) that can be showed by using addition and multiplication concepts. Student’s thinking on their level exhibited us their successful conservation when they were in the last grade. The progress of understanding by game, especially bermain satu rumah, is concrete effort to support number learning in primary school. Using game in learning process, for instance, mathematics learning for primary school can be a mathematics program for young children.